Novel approach to fabricating carbon nanotube via interconnects using size-controlled catalyst nanoparticles - Sato, S.; Nihei, M.; Mimura, A.; Kawabata, A.; Kondo, D.; Shioya, H.; Iwai, T.; Mishima, M.; Ohfuti, M.; Awano, Y. (Proceedings of the IEEE International Interconnect Technology Conference, 2006)
We propose a new approach to fabricating carbon nanotube (CNT) vias, which uses preformed catalyst nanoparticles to grow CNTs. A newly-designed impactor provided size-classified catalyst particles, and a new deposition system injected them into via holes down to 40 nm in diameter. The resultant CNT-via resistance was 0.59 Omega for 2-mum vias, which is the lowest ever reported, improved from the previous studies using catalyst films. The improvement resulted from higher-density CNTs grown in the via holes by employing the nanoparticle catalyst